ESP Class Activities to Boost Student Engagement in the Classroom: A Case Study (International Journal of Scientific Research and Management (IJSRM), 2023)
English for Specific Purposes (ESP) is regarded as a challenging course for students since it necessitates not only a solid foundation in basic English but also a strong understanding of professional topics in order for pupils to acquire this material effectively. The authors discovered that there was little student participation in class sessions when teaching ESP. Finding out why students don’t actively participate in class activities as well as what kinds of activities can encourage students to do so was the goal of the research. The study was carried out on a group of 24 English students majoring in human resource management at a university in Hanoi. After 6 weeks of face-to-face learning, activities to encourage student participation were applied. Both qualitative (interviews and discussions) and quantitative (surveys) methods are used in the research. The research team used a 5-level Likert Scale survey to collect information from students. Research results have shown the reasons why students limit their participation in activities, as well as the factors that help increase student participation in activities that lecturers deploy in the classroom.